ANALISIS MINAT KONSUMEN TERHADAP PEMBELIAN ULANG PRODUK COCA COLA KEMASAN BOTOL 1 LITER - Shiddiq, Jafar; Wahid, Abdul; Setiawanhengky.1999@gmail.com , Hengky (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2023)
According to data of CCAI (Coca Cola Amatil Indonesia) that opportunity of at home consumption is enormous, where as the market share of CCAI has only 13% of total drinking at home consumption. To support strategic for increasing at home consumption, CCAI has been doing home consumption business plan namely 1 liter’s bottle price drop from Rp.3000 to Rp.2700, giving Bell Soda Glass for each 3 closures of 1 liter’s bottle changed, increasing liter penetration in market, and continuing campaign of “Semangat” advertisement. Bell Soda Glass promotion begin from March 1 to August 31, 2000 that previous with reducing price on February 21, 2000 for all outlets. Then added other attributes have got from pre survey that might support 1 liter at home consumption. The research aims to identify a person’s Attitude toward a specific behavior is proposed to be a function of the perceived consequences of performing that behavior for repurchasing of 1 liter Coca Cola product and of the person’s evaluation of those consequences. Identify Subjective Norms is determined by the perceived expectations of specific referent individuals or groups, and the person’s motivation to comply with those expectations. Identify behavioral intentions are a function of the weighted sum of two variables are Attitude and Subjective Norms. This research uses survey method with questioner by respondent that had ever purchase 1 liter Coca Cola product that live at Yogyakarta and its environs according to company’s segmentation. The result of this research exhibited that consumer had good Attitude and supported to all consequences of 1 liter Coca Cola product, where as reference had a little influence for repurchasing of 1 liter Coca Cola product. The most dominant suggestion from reference that followed in repurchasing decision is the family’ s suggestion. The result, consumer is very intentions to repurchasing 1 liter Coca Cola product in given situation. The attribute has got the highest valuation is attribute for closure at that time is opened and can be closed again, and followed by attribute of Bell Soda Glass gift.